The abundance and geographic distributions of two species of ticks in South Australia: Bundey Bore revisited. (31st January 2023) - Teo, Ernest J. M.; Bull, C. Michael; Burzacott, Dale; Zalucki, Myron P.; Furlong, Michael J.; Barker, Dayana; Barker, Stephen C.
Abstract: Perhaps one of the central questions in ecology has been what limits the geographic distribution of species. The geographic distributions of the reptile‐ticks Amblyomma limbatum, Bothriocroton hydrosauri and Amblyomma albolimbatum are a classic example of this problem: where these ticks meet, narrow regions‐of‐overlap often occur. Despite studies of interactions among these ticks, and of these ticks and their environment, we still do not understand what limits their geographic distributions. Many hypotheses have been proposed and tested, but all have seemingly been rejected. Our aim was to account for the abundance and the geographic distributions of A. limbatum and B. hydrosauri at Bundey Bore Station, South Australia, where these species come in contact and have been studied for over 35 years, leading to over 55 000 records of reptiles and their ticks using a capture‐mark‐recapture approach. We constructed models which had combinations of temperature and moisture indices from different months of the year to determine the relationship between climate and tick abundance, and between climate and the shifting local geographic distribution of A. limbatum and B. hydrosauri at Bundey Bore Station. We found that climate together with the abundance of ticks in the previous year and the abundance of the lizard host, accounted for 54%–77% of the variation in the abundance of A. limbatum and B. hydrosauri among years. We also found that the climate in late autumn to winter, together with the abundance of ticks and their host, accounted for 18%–84% of the variation in the geographic distributions of these ticks among years. Climate was central to the abundance and the geographic distributions of A. limbatum and B. hydrosauri at Bundey Bore Station. We speculate that the same mechanisms account for the geographic distributions of A. limbatum, B. hydrosauri and A. albolimbatum elsewhere in Australia; so, climate may explain the three‐tick problem in Austral ecology. Abstract : We investigated the effects of climate on the abundance and the geographic distribution of ticks at Bundey Bore Station. We found that climate and various aspects of the abundance of ticks and their lizard host accounted for a substantial amount of the variation in the abundance and the geographic distribution of the two species of ticks.